Al-Tasyri' al-Qur'ani: Baina al-I'jaz wa Dalil Mashdarihi al-Rabbani - Baihaqi, Yusuf (al-'adalah, 2014)
Abstract: The legislation of the Qur’an: Between the Miracles of the Qur’an and the Nature of Rabbaniyatul Qur’ân (the Divine Aspects of the Qur’an). The study about the miracles of the Qur’an has been done by many scholars of the Qur’an. Among the scholars themselves one may find many interpretations; Some of them limit on the its linguistical aspects while others add some aspects to the content of the Qur’an. The discourses about the miracles of the Qur’an, then, continues to grow until today. To find common ground in reconciling these differences, one needs to first understand the nature of “miracles of the Qur’an” and the nature of “rabbaniyyatul Quran”/the divine aspects of the Qur’an. The miracles of the Qur’an can be seen as a sign that it comes from God, while the truth of the Qur’an that comes from God is not a part of the miracles. The hotchpotch between the two natures is, then, caused much confusion in the study of the Qur’an.Keywords: the Qur’anic legislation, the miracles of the Qur’anAbstrak: al-Tasyrî’ al-Qur’âni: Antara Mukjizat Alquran dan Argumentasi Hakikat Rabbaniyatul Qur’ân. Kajian seputar aspek kemukjizatan Alquran telah banyak dilakukan. Para ulama pun memiliki banyak penafsiran tentang itu; ada yang membatasinya pada aspek bahasa dan ada pula yang menambahkan aspek-aspek lain dari kandungan Alquran. Diskursus tentang kemukjizatan Alquran pun terus berkembang hingga masa kini. Untuk mencari titik temu dalam mendamaikan perbedaan pandangan ini, seseorang perlu terlebih dahulu memahami hakikat “mukjizat Alquran” dan hakikat “rabbaniyyatul Qur’ân”. Kemukjizatan Alquran merupakan pertanda bahwa ia bersumber dari Tuhan, sedangkan kebenaran Alquran yang bersumber dari Tuhan bukanlah pertanda akan kemukjizatannya. Pencampuradukkan antara dua hakikat di atas inilah yang kemudian menimbulkan banyak kerancuan dalam kajian Alquran.Kata Kunci: tasyrî` al-Qur’ân, I`jâz al-Qur’an